2022
DOI: 10.1038/s41598-022-16595-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel magnetic compression technique for cystostomy in rabbits

Abstract: Magnetic compression technique (MCT) is a popular new anastomosis method. In this paper, we aimed to explore the feasibility of use of MCT for performing cystotomy in rabbits. The parent magnets and daughter magnets for rabbit cystostomy were designed and manufactured according to the anatomical characteristics of rabbit lower urinary tract. Twelve female New Zealand rabbits were used as animal models. After anesthesia, a daughter magnet was inserted into the bladder through the urethra, and the parent magnet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…During the former procedure, the tissues at both ends of the anastomosis are subjected to limited “point” forces, whereas, during magnamosis, they are subjected to continuous “surface” forces. Based on these characteristics of magnamosis, it is also referred to as “smart anastomosis” 20 . Some studies have established that magnamosis is associated with less inflammation, scar, distortion, and mural thickening than suture and staple anastomosis owing to the lack of foreign bodies at the anastomotic site 21 .…”
Section: Discussionmentioning
confidence: 99%
“…During the former procedure, the tissues at both ends of the anastomosis are subjected to limited “point” forces, whereas, during magnamosis, they are subjected to continuous “surface” forces. Based on these characteristics of magnamosis, it is also referred to as “smart anastomosis” 20 . Some studies have established that magnamosis is associated with less inflammation, scar, distortion, and mural thickening than suture and staple anastomosis owing to the lack of foreign bodies at the anastomotic site 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Past researchers have found that magnamosis can be applied for any anastomosis involving a lumen in the digestive tract, including esophageal 11 , esophagogastric 12 , gastrojejunal 13 , 14 , small intestine 15 , colon 16 , and biliary-enteric anastomosis 17 . Magnamosis can be used for vascular anastomosis 18 , 19 as well as for creating therapeutic 20 and pathological 21 fistulas.…”
Section: Introductionmentioning
confidence: 99%
“…MCA has been under development for over 40 years, and its research fields have expanded from the initial vascular anastomosis and gastrointestinal anastomosis to ureterovesical anastomosis 5 , biliary stricture after liver transplantation 6 , 7 , esophageal stricture 8 , colorectal stricture 9 , and rectovaginal fistula closure repair 10 . MCA can also be used for therapeutic purposes of vesicostomy 11 and established pathological fistula animal models 12 .…”
Section: Introductionmentioning
confidence: 99%